ARE CLINICAL MEASURES OF CERVICAL SPINE STRENGTH AND CERVICAL FLEXOR ENDURANCE RISK FACTORS FOR CONCUSSION IN ELITE YOUTH ICE HOCKEY PLAYERS?. Issue 7 (11th March 2014) - Schneider, K; Emery, CA; Kang, J; Meeuwisse, W
Abstract : Background: Symptoms of dizziness, neck pain and headaches have previously been identified as risk factors for concussion. Clinical measures associated with these symptoms have not previously been evaluated as risk factors for concussion. Objectives: To evaluate clinical measures of cervical endurance and strength as risk factors for concussion in elite youth ice hockey players. Design: Prospective cohort study. Setting: Community ice rinks and Sport Medicine Clinic. Participants: Bantam (12-14 years) and Midget (15–17 years) male and female elite youth ice hockey players (n=466). Risk factor assessment: Participants completed baseline clinical tests of cervical flexor endurance and cervical spine isometric strength at the beginning of the 2011–2012 season. Main outcome measurements: Players with a suspected concussion (identified by team therapists) were referred to the study sport medicine physician for assessment (diagnosed as per the 3 rd International Consensus on Concussion in Sport Guidelines). Results: Concussion incidence rate ratios were estimated using Poisson regression (adjusted for cluster by team and exposure hours). 466 elite youth ice hockey players completed clinical baseline tests at the start of the 2011–2012 hockey season. Players performing in the lowest 25 th percentile were not at an increased risk of concussion during the season of play [cervical strength right sided IRR=1.33 (95%CI; 0.98–1.83); left IRR=1.07 (95% CI; 0.64–1.78] or cervical flexor endurance [IRR=1.27 (95% CI; 0.74–2.20)]. Conclusion: Clinical tests of cervical flexor endurance and isometric cervical strength were not predictive of concussion risk. Further evaluation of other baseline clinical measures is necessary to inform future development of prevention strategies for concussion in youth.